THE SOCIO-ECONOMIC RELEVANCE OF TRADITIONAL THRIFT AND CREDIT ASSOCIATIONS IN CONTEMPORARY NIGERIAN SOCIETY - ROBERT MARTINS EZE (International Studies Journal)
This paper examined the socio-economic relevance of traditional thrift and credit associations in contemporary Nigerian society. The thrift and credit associations have remained vital in Nigeria, considering the mass poverty ravaging the rural population, and they are also relevant as they have helped many families rise above the poverty line. This paper is conceptual, as secondary data were used. Empirical studies were consulted, and structural-functionalism was employed to understand the subject. The paper concluded that thrift and credit associations have played and continue to play a significant role in the socio-economic development of the rural and urban economies in contemporary Nigeria, given that many cottage industries, petty businesses, and many families have been lifted out of poverty, especially in the rural areas. This study recommended that the government should provide more funds to strengthen the thrift and credit associations to expand their scope to accommodate more members and reduce unemployment and poverty in Nigeria. The paper further recommended that membership in thrift and credit associations be open to vulnerable members of society irrespective of gender, age, and ethnicity.